LEARNING COMMUNITY IN LEARNING ENGLISH SPEAKING SKILLS - Muhammad Bambang Purwanto; Despita (Relawan Jurnal Indonesia, 2022)
: Learning Community in Learning English Speaking Skills at Junior High School 4 Sungai Lilin. One of the methods that can be applied in an effort to develop students ' ability to speak is learning community (community learning and studying together). Learning community is a concept of creating s hared learning in school, the learning process between teachers and teachers , teachers and students , students with students , and even among the school community with the community outs ide the school. This study aimed to describe the extent to which the effectiveness of the learning community in learning English s peaking s kills high school students of class IX Junior High School 4 Sungai Lilin, measured using deseign research that is an experimental type of pretest-posttest control group design experiments. Furthermore, data were collected using observation and oral tests were analyzed using descriptive statistics and inferential statistics. The results showed that the learning community is effectively used in improving the s kills of English s peaking high school students of class IX Junior High School 4 Sungai Lilin. It is based on the results of data analysis showed that the average test s peaking s kills of students who take classes that implement the learning in the learning community is higher than the results of the test speaking s kills of students who take the learning in the class room learning community that does not apply.